Penggunaan Media Simulasi PhET Model Problem-Based Learning (PBL) untuk Meningkatkan Keterampilan Proses Sains Peserta Didik - Suryanti, Eni (Papua Journal of Physics Education, 2023)
The purpose of this study was to determine the development of student’s science process skills (SPS) on parabolic motion material and to determine whether student’s science process skills can be significantly improved by using the Problem Based Learning (PBL) model assisted by PhET simulation. This research was conducted using a pre-experimental method using an initial assessment with a single group initial assessment design and a final assessment. The sampling method was carried out using cluster random sampling. Respondents who participated in this study were 20 students of class X-4 SMAS YPPK Taruna Dharma Kotaraja. The process of identifying the development of student’s SPS was analyzed based on the normalized profit analysis and whether there was a significant increase in SPS was analyzed by the one-group T-test of the initial assessment and the final assessment. The results of this study indicate that student’s science process skills increased based on the one-group T-test of the initial assessment and the final assessment, manual calculations (microsoft excel). Based on the results of the one-group T-test analysis of the initial assessment and the final assessment, the average value of student’s science process skills increased from 56.9 to 8.459 with an N-gain of 0.708873134. These results indicate that: 1) the science process skills of SMAS YPPK Taruna Dharma Kotaraja students have increased significantly after using PhET simulation media with PBL model on parabolic motion material, with a high category and 2) the use of PhET simulation media with PBL model on parabolic motion material is able to improve the science process skills of SMAS YPPK Taruna Dharma Kotaraja students.